Contemporary Situation of FDI and its Determinants: Bangladesh Scenario - Sadekin, Md. Nazmus; Muzib, Md. Moniruzzaman; Al Abbasi, Al Amin (American Journal of Trade and Policy, 2016)
This paper examines the present FDI scenario of Bangladesh since 1971 along with an explanation of its significant trend. The various trend facilities, exemptions provided by the government of Bangladesh are also mentioned in the paper. Moreover, the paper also investigates those factors that are handle and affects current FDI situation using the annual data for 1996-2010. From the analysis, we found that market size, infrastructure facilities, trade openness, export promotion, labor cost and availability of skilled labor are the important factors that contribute most to affect FDI.
Keywords: Foreign Direct Investment; Export Promotion; Economic Development; Employment opportunity; Incentive